Synthesis and biological evaluation of new [1, 2, 4]triazolo[4, 3-a]pyridine derivatives as potential c-Met inhibitors. Issue 16 (15th August 2016) - Zhao, Junjun; Fang, Lei; Zhang, Xiaobing; Liang, Yan; Gou, Shaohua
Graphical abstract: Abstract: A series of [1, 2, 4]triazolo[4, 3- a ]pyrazine derivatives (4a –4i ) were designed, synthesized and evaluated for their c-Met kinase inhibition and antitumor activity against SNU5 gastric cell line in vitro. Among these compounds, 4d was found to show the highest activity against c-Met and high selectivity against the tumor cells which are believed to be dependent on the c-Met oncogene amplification, because4d selectively inhibited c-Met while had no effect on other 59 kinases. In vivo efficacy study on human gastric (MKN-45) and human non-small cell lung (NCI-H1993) tumor xenograft in nude mouse demonstrated that4d ·CH3 SO3 H had a better inhibiting activity than SGX-523 in a dose-dependent manner. When tested in mice, compound4d ·CH3 SO3 H was found to have biological half-lives and plasma exposure values higher than those of JNJ-38877605, and its long-term toxicity and acute toxicity turned out to be acceptable, all of which indicates that4d ·CH3 SO3 H is a desirable drug candidate.